INTERPRETASI DATA GEOMAGNETIK UNTUK MENDETEKSI SEBARAN BATUAN MENGANDUNG MINERAL LOGAM DI AWANG BANGKAL, KABUPATEN BANJAR - rudy hendrawan noor; Ishaq Ishaq (AL-ULUM: JURNAL SAINS DAN TEKNOLOGI, 2022)
Research has been carried out to detect the presence and distribution of rocks containing metallic minerals. Almost every object used every day contains metal elements, so the presence of metal is very important to support every human activity. The presence of metal minerals in nature is generally quite a lot, but the types of metallic minerals vary. The geomagnetic method is a geophysical method that can detect subsurface rocks containing metallic minerals based on the difference in the magnetic field between the rock and the surrounding rock. Processing of geomagnetic data obtained in the field begins with daily correction and correction of the earth's main magnetic field (IGRF). The correction results obtained are anomaly of the earth's magnetic field which is distributed horizontally on the surface. The results of the analysis in the form of local magnetic field anomalies (∆H) are divided into 3 (three) regions, the first having a value between -236.5 nT to -8 nT (nano tesla) as an area that has a high local magnetic field anomaly value. Second, the value of -377.2 nT to -236.4 nT as an area that has a moderate anomaly value. Third, the low anomaly values ranged from -778.4 nT to -377.1 nT. Areas that have high local magnetic field anomaly values are interpreted as ultramafic rocks, which are source rocks of nickel lateric deposits rich in ferromagnesian minerals, distributed in the southeastern part of the study area.